Sistem Pendukung Keputusan Penerima Kartu Indonesia Sehat Menggunakan Metode Analitycal Hierarcy Process - Indrayani, Lilis (Universitas Pancasakti, 2024)
Abstract The Healthy Indonesia Card (KIS) is an identity card for National Health Insurance participants which is managed by the Health Social Security Administering Agency (BPJS). KIS is a program whose members are taken from underprivileged communities and the provision of cards is determined by the government and payment of contributions is borne by the government. However, sometimes in society there are many discrepancies in who is entitled to receive assistance and who is not entitled to receive assistance because the selection is still manual and based on recommendations from the government. This is the background that gave rise to the idea of ​​creating a decision support system that could serve as a recommendation for selecting people who are entitled to receive KIS. The research design used is a Data Flow Diagram (DFD). The method used to carry out the selection process and obtain results is the Analytical Hierarchy Process (AHP) method. The results of the design provide calculation results for the ranking of those entitled to receive KIS, providing reports on people who are and are not entitled to receive KIS.